Hedging functions of extraposed that-clauses in English and declarative subject da-clauses in Croatian academic writing - Varga, Mirna (ExELL, 2025)
In academic writing stance is often conveyed by means of extraposed that-clauses (It is possible that the results were misinterpreted.). The impersonal form of a matrix predicate allows writers to express attitudes without assuming responsibility for the claim, which renders extraposition particularly convenient for hedging (Biber et al., 1999). The equivalent clause type in Croatian refers to declarative subject da-clauses (Moguće je da su rezultati krivo protumačeni.). The study examines the hedging potential of the target clauses in research articles in English and Croatian. Raising awareness of the way hedged stance is conveyed in cross-cultural academic writing may provide important implications for academic writing instruction particularly in a non-native English context.